2009
DOI: 10.1007/s10637-009-9349-y
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitory effects of tea polyphenols by targeting cyclooxygenase-2 through regulation of nuclear factor kappa B, Akt and p53 in rat mammary tumors

Abstract: Breast cancer has become the second leading cause of cancer-related deaths worldwide. The control of this disease can be achieved through chemoprevention, which refers to the consumption of synthetic or naturally occurring agents to block, reverse, or delay the process of tumor development. Tea (Camellia sinensis), the most widely consumed beverage, has shown promises in the field of cancer chemoprevention. Inhibition of tumorigenesis by green or black tea polyphenols has been demonstrated in various in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…These isoforms act as homodimers and were shown to form heterodimers in mice (Yu et al 2006). Since COX-2 is regulated by NF-κB, it became the target of anti-COX therapeutics (Lee et al 2004, Roy et al 2011, although the use of COX-2 inhibitors in BD is currently not recommended because its potential interactions with lithium may have severe side effects. Preliminary observations of COX-1 inhibitors, however, suggest beneficial effects on the depressive symptoms of bipolar patients (Fond et al 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…These isoforms act as homodimers and were shown to form heterodimers in mice (Yu et al 2006). Since COX-2 is regulated by NF-κB, it became the target of anti-COX therapeutics (Lee et al 2004, Roy et al 2011, although the use of COX-2 inhibitors in BD is currently not recommended because its potential interactions with lithium may have severe side effects. Preliminary observations of COX-1 inhibitors, however, suggest beneficial effects on the depressive symptoms of bipolar patients (Fond et al 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…9,10 Previous reports from the authors' lab have shown the chemopreventive potential of tea polyphenols in both in vivo and in vitro conditions. 11,12 Chemoprevention through the use of naturally occurring phytochemicals has emerged as a successful strategy for cancer prevention and treatment. 13 But one major drawback associated with these phytochemicals is their inefficient systemic delivery and bioavailability under in vivo conditions; hence, the applicability of chemoprevention to humans has met with limited success.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, a previous study from Kane et al [40] showed that red wine polyphenols reduced angiotensin II-induced COX-2 overexpression in rat vessels. Previous publications have also reported an inhibitory effect of red wine extract and tea polyphenols on COX-2 activity [20, 38]. However, a recent study evaluated the effect of several food polyphenols, including resveratrol, a component of red wine polyphenols, on the activity of COX-2 and reported that although these compounds could elicit the inhibition of COX–2, their potency was 100- to 1000-fold lower compared to known pharmacological inhibitors of COX-2 such as celecoxib and indomethacin [41].…”
Section: Discussionmentioning
confidence: 98%
“…In the present work, we found that Provinols reduced NF- κ B in the aorta, but not in SMA, accounting potentially for reducing COX-2 expression. Previously, it has been shown that tea polyphenols inactivated phosphorylated forms of nuclear NF- κ B and reduced COX-2 expression in rat mammary tumours [38]. Furthermore, procyanidin extracts, a mixture of polyphenols, inhibited NF- κ B (p65) translocation in lipopolysaccharide-stimulated macrophages [39].…”
Section: Discussionmentioning
confidence: 99%